(untitled) (Sebha University Conference Proceedings, 2024)
The petroleum industry produces significant amounts of oily wastewater, either through the process of oil production named associated water, through the process of oil refinery, or because of pipeline leakage through oil transportation. Environmentally permissible oily wastewater treatment is a major problem for the petroleum industry. Nowadays, the focus has been on the awareness of the treatment methods of oily wastewater. Therefore, oil-water separation has become a recent obstacle, and it must be explored and resolved by petroleum industries to meet set standards and protect the environment. However, during the last decades of growing urbanization and industrialization worldwide, the consumption of oils and their derivatives has significantly expanded. Due to some factors such as poor management, incomplete combustion, pipeline leakage, and other incidental circumstances, petroleum leaks into water and soil and are nearly unavoidable during the process of petroleum extraction, transportation, processing, and utilization. Since the relative toxicity of petroleum and its products, petroleum pollutants in water and soil can seriously harm the local ecosystem and human health. Therefore, efficient water and soil remediation technologies solutions for oil-contaminated sites are essential for environmental safety and sustainable growth. The current review of part-I focuses on the physical and chemical remediation technologies of oil-contaminated water.